KAJIAN SIFAT FISIKA TANAH PADA PERTUMBUHAN TANAMAN MANGGIS (Garcinia mangostana L.) DI KABUPATEN LIMA PULUH KOTA - Yulnafatmawita Yulnafatmawita; Adrinal Adrinal; Sudewi Isminingsih (Jurnal Solum, 2008)
This research was aimed to evaluate physical properties of soils grown by mangosteen crops in Lima Puluh Kota Regency, especially in Kecamatan Payakumbuh and Kecamatan Guguk, in West Sumatra.   Soils were sampled by using sample rings for undisturbed and by using soil driller for disturbed samples on 0-20, 20-40, and 40-60 cm soil depth.  Soil samples were analyzed in Soil Laboratory Agriculture Faculty, Andalas University, Padang.  The results showed that soil texture in two locations was similar, that was silty loam for the 0-40 cm depth, and clay for the 40-60 depth.  However, generally soil organic matter content in Guguk was lower than that in Payakumbuh, that was medium to low, BV from low to high, total porosity from high to medium, and permeability from high to slightly slow.  Key  Words: Soil physical properties, mangostana